A Study on High School Students’ Critical Thinking Skills - İnan Tekin; Ali Orhan (Sakarya University Journal of Education)
The aim of this non-experimental quantitative study which employed a survey design was to determine the level of high school students’ CT skills and to investigate if high school students’ critical thinking (CT) skills differ by gender, father and mother’s educational background, age, and grade level. Critical Thinking Skill Test for High School Students was used to collect data in this study carried out with 603 high school students. As a result of the study, it was found out that students had high CT skills in terms of each sub-tests. Also, it was found out that students’ CT skills significantly differed by gender and educational background of their father and mother. Females and students who have a father and mother with higher educational degrees had higher CT skills. However, age and grade level did not significantly affect students’ each sub-test scores and total test scores. These results of the current study were confirmed by the huge body of previous literature.